MSCF-LUNet: a lightweight three-stage pine wilt disease segmentation model with multi-scale context fusion mechanism - Zhou, Dejing; Chen, Junxian; Cai, Wenxi; Lin, Jie; Meng, Tiantian; Li, Yuanhang; Liu, Baihan; Luo, Mengting; Lan, Yubin; Liu, Tianyi; Zhao, Jing (Frontiers in Plant Science, 2026)
IntroductionPine wilt disease (PWD) is a highly destructive infectious disease that severely damages pine forests worldwide. Because symptoms emerge first in the tree crown, detection from unmanned aerial vehicles (UAVs) is efficient. However, most methods perform only binary classification and lack pixel-level staging, which leads to missed initial symptoms and confusion with other species.MethodsWe propose MSCF-LUNet, a lightweight three-stage semantic segmentation model based on multi-scale context fusion. The model uses an improved multi-scale patch embedding guided by attention with relative position encoding (AWRP) to adapt the sampling field of view and to fuse local details with global context. Under contextual attention, the network learns fine-grained features and location cues.ResultsIn complex environments, MSCF-LUNet achieves 89.56% precision, 92.13% recall, 88.92% intersection over union (IoU), and 96.54% pixel accuracy (PA), balancing performance and computational cost.DiscussionThe model effectively segments PWD-infected regions and determines disease stages from remote-sensing imagery.